Comparative cephalometric study of the airways between different ethnic groups with normal occlusion - Genesis ZAMBRANO; Jose Gregorio Pelayo GUERRA; Laura Dias SOVIERO; Renan Morais PELOSO; Felicia MIRANDA; Karina Maria Salvatore de FREITAS; Arnaldo PINZAN; Marcos Roberto de FREITAS (Dental Press Editora, 2024)
ABSTRACT Objective: This study aimed to compare the nasopharynx and oropharynx airway dimensions of Caucasians, Blacks, Japanese, Japanese Brazilians, and Black Caucasians. Methods: A sample of 216 lateral radiographs of untreated young Brazilian subjects (mean age of 12.94 years; SD 0.88) were divided into five groups: Black Caucasian, Black, Caucasian, Japanese, and Japanese Brazilian. Lateral radiographs were used to measure the oropharynx (from the midpoint on the soft palate to the closest point on the anterior pharyngeal wall) and the nasopharynx (from the intersection of the posterior border of the tongue and the inferior border of the mandible to the closest point on the posterior pharyngeal wall). Analyses of variance (ANOVA) and Tukey's test were performed (p< 0.05). Results: The linear dimension of the oropharynx was similar among the different ethnic groups. Caucasian individuals presented a significantly greater linear dimension of the nasopharynx than Black Caucasian and Black individuals. Conclusions: All the groups had similar buccopharyngeal values. However, Caucasian individuals had significantly higher values when compared to Black Caucasians and Black individuals.